Do soft soil layers reduce the seismic kinematic distress of onshore high-pressure gas pipelines? - Nikolaos Makrakis; Prodromos N. Psarropoulos; Anastasios Sextos; Yiannis Tsompanakis (Bulletin of Earthquake Engineering, 2024)
Onshore high - pressure gas pipelines constitute critical infrastructure that usually cross seismic - prone regions and are vulnerable to Permanent Ground Deformations (PGDs) due to active seismic faults. In design, it may not be feasible to avoid fault rupture areas due to various technical, economical and topographic reasons. Moreover, the presence of soil layers affects the PGDs resulting from a tectonic fault, which in turn may alter the seismic demand on the pipeline. The current study investigates numerically the impact of soft soil layers on the seismic kinematic distress of onshore gas pipelines. For this purpose, a decoupled numerical modeling approach is adopted, consisting of two separate finite - element models for the simulation of soil response and pipeline distress, respectively. Soil non - linearities are taken into account utilizing the Mohr - Coulomb constitutive model with isotropic strain softening. An extensive parametric analysis is performed considering different faulting mechanisms and fault dip angles, as well as soil geometry and mechanical properties. Consequently, the maximum absolute values of both tensile and compressive pipeline strains are correlated with the seismic intensity level (i.e., in terms of bedrock offset which is associated with earthquake magnitude via simple relationships). The paper concludes with a set of design charts and tables for the preliminary seismic design of onshore high - pressure gas pipelines. These charts and tables predict with reasonable accuracy pipeline deformations, in terms of strains, for different magnitude, fault type, dip angle, sand type, and varying overlying soil layer thickness.